Effects of Wx and Its Interaction With SSIII-2 on Rice Eating and Cooking Qualities - Yang, Bowen; Xu, Shunju; Xu, Liang; You, Hui; Xiang, Xunchao (Frontiers in Plant Science, 2018)
The Wx gene encodes a granule-bound starch synthase (GBSS) and plays a key role in determining rice eating and cooking qualities (ECQs). SSIII-2 (SSIIIa), a member of the soluble starch synthases, is responsible for the synthesis of long chains of amylopectin. To investigate the effects of Wx and its interaction with SSIII-2 on grain ECQs, a population from a hybrid combination was established as a research material. The genotypes of SSIII-2 and the single nucleotide polymorphisms (SNPs) on intron1, exon6, and exon10 of Wx, and the physicochemical indicators and rapid visco analyzer (RVA) profile characteristics were analyzed. The results revealed various effects of SSIII-2 on rice quality under different backgrounds of Wx alleles. There was no obvious difference between different SSIII-2 alleles under the same background of Wxa, whereas there was a significant diversity under the same background of Wxb. Wxa had a dominant epistasis to SSIII-2 because the effect of SSIII-2 was masked by the massive synthesis of GBSS under Wxa. The apparent amylose content (AAC) was mainly controlled by the In1G/T SNP, and rice gel consistency (GC) was regulated by the Ex10C/T SNP. The combined effects of three SNPs had a significant influence on all ECQs and RVA profile parameters, except for gelatinization temperature. In1T-Ex6A-Ex10C and In1T-Ex6A-Ex10T were classified as being low AAC type. TT-AA-CC and TT-AA-TT had a low AAC and a soft GC. The combined effects of different SNPs of Wx are very important for rice quality breeding.